2005
DOI: 10.1152/ajpregu.00034.2005
|View full text |Cite
|
Sign up to set email alerts
|

Repeated pregnancies (multiparity) increases venous tone and reduces compliance

Abstract: In humans, multiparity (repeated pregnancy) is associated with increased risk of cardiovascular disease. In rats, multiparity increases the pressor response to phenylephrine and to acute stress, due in part to changes in tone of the splanchnic arterial vasculature. Given that the venous system also changes during pregnancy, we studied the effects of multiparity on venous tone and compliance. Cardiovascular responses to volume loading (2 ml/100 g body wt), and mean circulatory filling pressure (MCFP, an index o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
2
15
0
Order By: Relevance
“…The hormonal changes that take place during pregnancy may affect the handling of electrolytes, volume expansion and resultant vasodilation (Brenner et al, 1972). All of these may invariably affect the cardiovascular system (Dhawan et al, 2005) and by implication the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormonal changes that take place during pregnancy may affect the handling of electrolytes, volume expansion and resultant vasodilation (Brenner et al, 1972). All of these may invariably affect the cardiovascular system (Dhawan et al, 2005) and by implication the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy affects the endocrine (Banaczek, 1995), cardiovascular (DHawan et al, 2005) and other systems especially the renal system since it displays hypertrophy of functions, altered homeostasis and haemodynamic leakage of some substances as well as exaggerated response to posture (Korda, 1987). Many nephrologists believe in the possibility that prolonged period of increased single nephron filtration as in grandmultiparity may exert potentially damaging effect on the glomerulus especially the hyperfiltration and increased glomerular blood pressure (Hostetter et al, 1892).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have shown that multiparity leads to increased vascular stiffness, venous tone and endothelial dysfunction, and that these changes may be related to increased formation of reactive oxygen species and decreased availability of nitric oxide (NO) [9,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Future studies should examine whether such a multifaceted intervention would alter the Phe and KCl contractions in rat veins, suggesting a role of endothelium-derived factors or that the responses would be similar in veins treated with blockers of endothelium-derived vasodilators and nontreated veins, suggesting mainly endotheliumindependent mechanisms. (19). Multiparity could also affect venous tone and compliance.…”
Section: Diltiazemmentioning
confidence: 99%
“…These observations have led to the suggestion that repeated pregnancy could cause reduction in splanchnic venous compliance and augment splanchnic venous reactivity and sympathetic control of venous tone. This could, in turn, compromise the ability of the capacitance venous system to accommodate volume overload or changes in cardiac preload (19). Therefore, the effects of multiple pregnancies on the Ca 2ϩ -dependent and Ca 2ϩ -sensitization mechanisms of venous contraction should be examined in future studies.…”
Section: Diltiazemmentioning
confidence: 99%